2017
DOI: 10.1002/adma.201703863
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Deformed MoS2for Electrochemically Stable, Thermally Resistant, and Highly Efficient Hydrogen Evolution Reaction

Abstract: The emerging molybdenum disulfide (MoS ) offers intriguing possibilities for realizing a transformative new catalyst for driving the hydrogen evolution reaction (HER). However, the trade-off between catalytic activity and long-term stability represents a formidable challenge and has not been extensively addressed. This study reports that metastable and temperature-sensitive chemically exfoliated MoS (ce-MoS ) can be made into electrochemically stable (5000 cycles), and thermally robust (300 °C) while maintaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(85 citation statements)
references
References 58 publications
1
84
0
Order By: Relevance
“…In particular, the layer spacing of 2H MoS 2 is reduced . Figure f showed the Raman spectra of the obtained 1T MoS 2 NFs, 2H MoS 2 (after annealing), and bulk MoS 2 , where the three main characteristic peaks in 376, 403, and 449 cm −1 are consistent with the E 1 2g , A 1 g , and second‐order Raman scattering 2LA(M) modes of MoS 2 ,,. More important, two additional peaks around 190 and 218 cm −1 were found in the obtained MoS 2 NFs, which is consistent with literature for 1T MoS 2 ,,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the layer spacing of 2H MoS 2 is reduced . Figure f showed the Raman spectra of the obtained 1T MoS 2 NFs, 2H MoS 2 (after annealing), and bulk MoS 2 , where the three main characteristic peaks in 376, 403, and 449 cm −1 are consistent with the E 1 2g , A 1 g , and second‐order Raman scattering 2LA(M) modes of MoS 2 ,,. More important, two additional peaks around 190 and 218 cm −1 were found in the obtained MoS 2 NFs, which is consistent with literature for 1T MoS 2 ,,…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, plenty of investigations have been devoted to the construction and design of highly efficient and active MoS 2 ‐based catalysts. The morphology design of MoS 2 nanostructures has proven to be an efficient strategy to increase the active sites, such as hierarchical nanosheet‐based MoS 2 nanotubes, core‐shell MoO 3 ‐MoS 2 nanowires, MoS 2 nanoparticles/graphene composites, single layer 1T‐phase MoS 2 nanosheets, alloyed MoS 2x Se 2(1‐x) nanotubes, porous MoS 2 nanosheets, vertical MoS 2 nanoflakes, crumpled MoS 2 , and MoS 2 nanoflowers (NFs), etc. Among them, MoS 2 NFs have attracted significant attentions due to the high surface to volume ratio and rich active sites for enhanced HER performance.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in strain engineering of 2D TMDs have shown that their electronic band structure is sensitive to strain, and could be used to tune the contact resistance at semiconductor–metal interfaces. Some work has demonstrated that strain engineering can also be used to improve the HER activity of TMDs by modifying Δ G H . Therefore, care must be taken to separate out the effects of strain on thermodynamics and charge injection.…”
Section: Resultsmentioning
confidence: 99%
“…For the hydrogen evolution reaction (HER), the Sabatier principle plots the catalytic activity of solid‐state catalysts as a function of the Gibbs free energy of hydrogen adsorption (Δ G H ) to a catalytic site and predicts optimal catalytic activity when Δ G H is close to zero . Many transition metal dichalcogenides (TMDs) have been investigated as potential electrocatalysts, including MoS 2 that exhibits small Δ G H , which has led to extensive effort to use MoS 2 as an HER catalyst via nanostructuring, strain‐engineering, and phase‐engineering . However, Δ G H alone does not determine the overall HER activity; charge injection into MoS 2 has a large effect on catalytic efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40] It is also reported that introducing MoO 3 into the basal plane of MoS 2 or fabricating aM oO x /MoS 2 core-shell nanostructure can enhance the HER activity. [41][42][43] In addition, phase transitions in the basal plane [44][45][46] and structurally deformed on MoS 2 [47,48] are important methods to enhancet he HER performance by activating basal planes. Despite the great progress achieved so far,v ery few studies have attempted to activate basal planes by effectively and controllably introducing pores on the basal planes.…”
Section: Introductionmentioning
confidence: 99%